2019
DOI: 10.1016/j.jmsy.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

smaRTI—A cyber-physical intelligent container for industry 4.0 manufacturing

Abstract: Cyber-Physical Systems (CPSs) are becoming a significant research focus resulting from advancements in technologies such as the Internet of Things (IoT), Cloud Manufacturing and Intelligent Products. Successful deployment of CPSs has the potential to provide a step change in manufacturing efficiency, flexibility and production yield as envisaged by the fourth industrial revolution or Industry 4.0 paradigm. The realisation of intelligent products and services is in the provisioning of predictive, risk preventat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 48 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Opt_nodes set ← UDAS_D i (11) delete UDAS_D i from UDAS_D (12) end-if (13) end-for (14) return Opt_nodes set ALGORITHM 2: Data storage node selection. 4 Mobile Information Systems shorter than that of baselines, and the data access time increases slowly.…”
Section: Random Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…Opt_nodes set ← UDAS_D i (11) delete UDAS_D i from UDAS_D (12) end-if (13) end-for (14) return Opt_nodes set ALGORITHM 2: Data storage node selection. 4 Mobile Information Systems shorter than that of baselines, and the data access time increases slowly.…”
Section: Random Topologymentioning
confidence: 99%
“…At present, industry 4.0 not only takes intelligent development as the primary target but also extensively applies advanced measures such as information technology, information interaction, and process reengineering. Based on meeting the personalized and di erentiated needs of di erent consumers, exible production is performed to achieve maximum decision optimization [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers in Logistics 4.0 mention just one (primary) industrial sector. However, other papers mention more than one application field; this is for instance the case for multiple case studies [37,57,58]. Therefore, the total number of applications is higher than the number of studies examined.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…To be more effective, however, Figure 6 is limited to the industrial sectors that presented at least three application papers. In total, eighteen different industrial sectors were identified in the sample of papers examined; those not shown in Figure 6 are: courier [59,60] agriculture [61,62] and electrical [51,57] -with two papers each; serious games [54], packaging [53], maintenance, repair and operations parts [63], petroleum [57] and jewellery [64] -with only one paper each. From Figure 6 it can be seen that 70 papers do not indicate any specific application field for Logistics 4.0.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…These are expressed formally in the RFID SCO. The part of the tagging entity that can be tagged has to have at least one surface available for tagging, which can be identified by either an end user or a simulation tool (Neal et al ., 2019). The set of surfaces recommended for tagging is a subset of the surfaces available for tagging and is determined by the position of the reader antenna.…”
Section: The Ontology Development Processmentioning
confidence: 99%